Distribution of Accumulation Measured by the snow Stake Method in Mizuho Plateau - Yamada, T.; Okuhira, F.; Yokoyama, K.; Watanabe, O. (1978)
P(論文) The seasonal and the annual variations of accumulation of snow and its regional distribution were measured by means of snow stakes distributed along the various traverse routes in Mizuho Plateau, East Antarctica, in 1968-1974. The deposition of snow occurs mainly in the winter season from February to September; on the contrary, the erosion of snow occurs in the summer season from November to January. Maximum values of accumulation rate were found at both the equinoxes. As for the coastal region between 1000m and 1700m a. s. l., the maximum annual accumulation during seven years from 1968 to 1974 was observed in 1970,which is about 2.5 times larger than the minimum which was observed in 1969. The firn line and the dry snow line are located in Mizuho Plateau, respectively at 400-500m at 700-1000m a. s. l. As for the region between 1700m and 3500m a. s. l., hiatuses in accumulation were usually found. The modes of regional distribution of annual accumulation differ sharply from each other among the five regions, which are divided at the boundaries located at 400-500m, 700-1000m, 1700-1900m and 3400-3500m a. s. l. departmental bulletin paper